Numerical modeling of the fractional-differential dynamics of the filtration-convective diffusion on the base of parallel algorithms for cluster systems - Bogaenko, V.A.; Bulavatsky V.М. (Reports of the National Academy of Sciences of Ukraine, 2017)
Within the framework of the fractional-differential mathematical model of an abnormal convective-diffusion process under conditions of a mass-transfer and a plane filtration field, the statement of the conforming two-dimensional non-stationary boundary-value problem is executed, and the finite-difference technique of obtaining its approximated solution, founded on application of a locally one-dimensional method in the field of a complex potential flow is described. The parallel algorithms of solving the problem on cluster systems are designed, the results of their performance testing and the results of numerical experiments on a simulation of the dynamics of the studied process are presented.